RANCANG BANGUN SISTEM INFORMASI PENGARSIPAN SURAT MASUK DAN KELUAR DI KEMENTERIAN AGAMA KABUPATEN ENDE - Nofita, Dela (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Archive is a record of “record or warkat” written, printed or typed in the form of letters, numbers, pictures that have a certain meaning and purpose as material for communication and information. The Ende Regency Ministry of Religious Affrais Office still manages the archiving of incoming and outgoing letters conventionally/manually written using ledgers and archived on file shelves. The purpose of this study is to design and build an information system for filing incoming and outgoing letters at the Ministry of Religious Affairs of Ende Regency. The software design methodology used in this study is UML (Unified Modelling Language). In this study, researchers used qualitative methods by collecting data in the form of detailed stories or actual circumstances. With this archiving information system, it can ficilitate the filing of incoming and outgoing mail so as to minimize the sime used, streamline and streamline the existing place or space. Keywords : Archive, Letter, Uml, Qualitative.